Microeconomic Analysis of Bitcoin Pricing and Establishing Theoretical Conditions for the Possibility of a Bubble or a Crash - Shah, Ketan K. (Indian Journal of Research in Capital Markets, 2018)
Crypto currencies are becoming popular on the digital platform as a medium of exchange and more as a store of value, specifically to satisfy the speculative motive. Bitcoin is one such and the trendiest crypto currency which is in news due to considerable volatility observed in its price in recent times. This paper began by examining the history of bitcoin and questioning whether the volatility in its price is yet another bubble in the making. After distinguishing bitcoin from traditional currencies, this paper examined the process of bitcoin price determination from a pure microeconomic point of view using the popular demand and supply cross diagram as a tool and deduction as a methodology and established theoretical conditions that can lead to a bitcoin price bubble or a crash. Here, the concept of price elasticity of demand and supply is brought into play to understand stable and unstable equilibrium. The paper also debated about the possibility of valuation of bitcoin and warned the governments and investors about the damaging potential of this currency in upsetting their goals with reference to regulation and investment returns, respectively.